Resistência e recriação camponesa a partir do programa de aquisição de alimentos no município de Lagoa Seca - PB - Souza, Jamerson Raniere Monteiro de (2015)
Family agriculture in Brazil, historically passed over by the government, it is still important in terms of generating output and employment. The resistance and peasant recreation is a phenomenon that has challenged researchers from various fields of knowledge. The advance of capitalism in the countryside, although it has accelerated the concentration of lands and dispossessed small farmers, failed to completely destroy peasant production. Family agriculture in the city of Lagoa Seca-PB is in the middle of this conflict. A major problem faced is the marketing of products, dominated by the action of middlemen, who appropriate the surplus. Therefore, public policies, aimed at the institutional market, have proven mitigating this process of exploitation. The Programa de Aquisição de Alimentos (PAA), which acquire products directly from family farms to help people in a social vulnerability, emerges as an important element in this way to keep the production, resistance and recreating. In this context, the research aims to discuss the forms of resistance and adaptation of peasant agriculture in Lagoa Seca-PB, highlighting the role played by the PAA. The dissertation brings back the classic and current debate about the disintegration of the peasantry versus their ability to reproduce / recreate. It emphasizes the impacts of public policies of the federal government regarding the resistance / recreation of "family agriculture". In particular it analyzes the action of the PAA in Lagoa Seca-PB as an alternative to this process. The following methodological procedures were used: bibliographical research; documentary research on the program; survey of census data; and field research that included: visits to production and marketing units. Also were made twenty-four semi-structured interviews with family farmers, middlemen and the people responsible for the program in the city. The analysis results showed the importance of the PAA for support of peasant production in Lagoa Seca city, although still restricted in terms of benefit productive units and the value of the quota of each producer.